Associations between genetic variants of Toll-interacting proteins and interstitial lung diseases: a systematic review and meta-analysis - Xiaoyuan Li; Beibei Cui; Lili Jiang (Orphanet Journal of Rare Diseases)
Abstract Background Genetic polymorphisms in Toll-interacting protein (TOLLIP) have been documented in relation to clinical manifestations of interstitial lung disease (ILD). Nevertheless, the findings across studies present inconsistencies. The present meta-analysis endeavors to elucidate the nexus between genetic variations in TOLLIP and the onset and prognosis of interstitial lung disease (ILD), with the overarching aim of providing insight into the pathophysiological underpinnings of ILD. Method This systematic review was registered in PROSPERO. The OVID MEDLINE, OVID EMBASE, and Web of Science electronic databases were searched. Results Fourteen studies with a total of 4821 cases and 9765 controls were examined. The final TOLLIP variants to be included in this meta-analysis were rs5743890, rs111521887, and rs3750920. There were significantly fewer TOLLIP rs5743890 minor allele C carriers among individuals with interstitial lung disease (ILD) than among those without this condition (11.42% vs. 18.92%). Conversely, patients with ILD exhibited higher frequencies of rs111521887 minor allele G carriers (28.92% vs. 22.44%) and rs3750920 minor allele T carriers (40.06% vs. 34.00%). A potential association between rs5743890_C and a reduced incidence of ILD was plausible (p = 0.04, OR = 0.72, 95% CI = 0.53–0.99). Furthermore, a stratified analysis revealed that rs5743890_C was significantly associated with a decreased risk of IPF (p = 0.004, OR = 0.62, 95% CI = 0.44–0.86). There was a significant correlation between susceptibility to ILD and rs111521887 G (p < 0.00001, OR = 1.48, 95% CI = 1.33–1.65) and rs3750920 T (p < 0.00001, OR = 1.34, 95% CI = 1.26–1.44). The survival of IPF patients was correlated with the TOLLIP rs5743890 SNP, and patients with the rs5743890_C genotype had worse survival (p = 0.02, HR = 1.59, 95% CI = 1.07–2.36). Conclusion This study showed that rs5743890_C was associated with a lower incidence of ILD and a worse survival rate in patients with IPF. Rs111521887_G and rs3750920_T were found to be associated with an elevated risk of ILD incidence, while no significant association was observed with ILD prognosis. Furthermore, studies are warranted to validate our results and assess the effects of TOLLIP genetic variants on ILD.